A Methods engineering study on SC&C Cosmetech, Co. Inc. - Argomido,Lanie; Cagape, Adonis; Lagrosa, Maria Lareza; Santos, Hannah Ruth. (Diliman, Quezon City College of Engineering, 2003)
SC&C Cosmetech, Co., Inc. manufacturer of Johnson and Johnson's products, has been chosen as the study site. The core of the study is on method's improvement and design, which is helpful to the company since its operations are mostly semi-automated. Interviews with the Manager and Supervisor were conducted during the initial visits. Documentation were also done by the group. Several plant visits and time study were conducted and problems were identified.These problems were categorized into major and minor problems. Further discussions and analysis lead to the identification of major and minor problems. The major problems are poor work design, lack of manpower, non-motivating environment, and machine problems like coding machine failure, plugging and filling machine problem. For the problem of poor work design, the group proposed that the equipment and tools need to be redesigned. This will provide ease and comfort to the workers. It may result to the improved performance of the workers and increase in the efficiency of the production. However, this may result to additional cost on the part of the management. On the other hand, redesigning does not cost as much as buying new equipment. A design of the equipment was recommended by the group. The problem of lack of manpower could be resolved by hiring additional workers. This will cost Php12,450.00 salary expense to the company but an increase in the efficiency of the production of about 80.49 percent with 74 bottles per minute. Implementing a third shift was also proposed. It will lessen the salary expense of the company by Php3,135.00 per day. On the other hand, the management has to hire another Supervisor. The additional salary in hiring can be obtained from the saved salary expense. The non-motivating work environment problem could be resolved by providing background music in the production area. It can enhance a lively atmosphere since the work is tedious. Installation of down lighting type of light source in the storage area is also proposed to prevent accidents in the storage area especially during the night when there is not enough lighting. For the machine problems, implementing a preventive maintenance rather than remedial maintenance is proposed. It will ensure a greater probability of uninterrupted production. Making use of visual or audio signal such as red light or buzz in the filling machine is proposed so that when the pressure reaches the critical level, low pressure occurrences will lessen. Moreover, a monthly machine over all checkup can ensure that the machines are in good condition aside from preventing the unexpected occurrence of machine breakdown. Due to time constraints, several areas for further studies were proposed. These include redesigning of the conveyor and time studies on material handling and mixing operations.
IE 32
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis